Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Discover reliable solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
To find [tex]\( g \circ f \)[/tex] (denoted as [tex]\( gof \)[/tex]), we need to determine the composition of the functions [tex]\( f \)[/tex] and [tex]\( g \)[/tex]. The composition [tex]\( gof \)[/tex] is defined such that for each [tex]\( x \)[/tex] in the domain of [tex]\( f \)[/tex], we find [tex]\( f(x) \)[/tex], and then apply [tex]\( g \)[/tex] to the result of [tex]\( f(x) \)[/tex].
We start with the function [tex]\( f \)[/tex] given as:
[tex]\[ f = \{(1, 2), (3, 5), (4, 1)\} \][/tex]
And the function [tex]\( g \)[/tex] given as:
[tex]\[ g = \{(2, 3), (5, 1), (1, 6)\} \][/tex]
Let's evaluate step by step:
1. For the pair [tex]\( (1, 2) \)[/tex] in [tex]\( f \)[/tex]:
- [tex]\( f(1) = 2 \)[/tex]
- Now, find [tex]\( g(2) \)[/tex]:
[tex]\[ g(2) = 3 \][/tex]
- So, for [tex]\( x = 1 \)[/tex], [tex]\( g(f(1)) = g(2) = 3 \)[/tex]
- Thus, one element in [tex]\( gof \)[/tex] is [tex]\( (1, 3) \)[/tex]
2. For the pair [tex]\( (3, 5) \)[/tex] in [tex]\( f \)[/tex]:
- [tex]\( f(3) = 5 \)[/tex]
- Now, find [tex]\( g(5) \)[/tex]:
[tex]\[ g(5) = 1 \][/tex]
- So, for [tex]\( x = 3 \)[/tex], [tex]\( g(f(3)) = g(5) = 1 \)[/tex]
- Thus, another element in [tex]\( gof \)[/tex] is [tex]\( (3, 1) \)[/tex]
3. For the pair [tex]\( (4, 1) \)[/tex] in [tex]\( f \)[/tex]:
- [tex]\( f(4) = 1 \)[/tex]
- Now, find [tex]\( g(1) \)[/tex]:
[tex]\[ g(1) = 6 \][/tex]
- So, for [tex]\( x = 4 \)[/tex], [tex]\( g(f(4)) = g(1) = 6 \)[/tex]
- Thus, another element in [tex]\( gof \)[/tex] is [tex]\( (4, 6) \)[/tex]
Combining all the elements we found, we get:
[tex]\[ gof = \{(1, 3), (3, 1), (4, 6)\} \][/tex]
So, the correct answer is:
[tex]\[ \boxed{\{(1, 3), (3, 1), (4, 6)\}} \][/tex]
We start with the function [tex]\( f \)[/tex] given as:
[tex]\[ f = \{(1, 2), (3, 5), (4, 1)\} \][/tex]
And the function [tex]\( g \)[/tex] given as:
[tex]\[ g = \{(2, 3), (5, 1), (1, 6)\} \][/tex]
Let's evaluate step by step:
1. For the pair [tex]\( (1, 2) \)[/tex] in [tex]\( f \)[/tex]:
- [tex]\( f(1) = 2 \)[/tex]
- Now, find [tex]\( g(2) \)[/tex]:
[tex]\[ g(2) = 3 \][/tex]
- So, for [tex]\( x = 1 \)[/tex], [tex]\( g(f(1)) = g(2) = 3 \)[/tex]
- Thus, one element in [tex]\( gof \)[/tex] is [tex]\( (1, 3) \)[/tex]
2. For the pair [tex]\( (3, 5) \)[/tex] in [tex]\( f \)[/tex]:
- [tex]\( f(3) = 5 \)[/tex]
- Now, find [tex]\( g(5) \)[/tex]:
[tex]\[ g(5) = 1 \][/tex]
- So, for [tex]\( x = 3 \)[/tex], [tex]\( g(f(3)) = g(5) = 1 \)[/tex]
- Thus, another element in [tex]\( gof \)[/tex] is [tex]\( (3, 1) \)[/tex]
3. For the pair [tex]\( (4, 1) \)[/tex] in [tex]\( f \)[/tex]:
- [tex]\( f(4) = 1 \)[/tex]
- Now, find [tex]\( g(1) \)[/tex]:
[tex]\[ g(1) = 6 \][/tex]
- So, for [tex]\( x = 4 \)[/tex], [tex]\( g(f(4)) = g(1) = 6 \)[/tex]
- Thus, another element in [tex]\( gof \)[/tex] is [tex]\( (4, 6) \)[/tex]
Combining all the elements we found, we get:
[tex]\[ gof = \{(1, 3), (3, 1), (4, 6)\} \][/tex]
So, the correct answer is:
[tex]\[ \boxed{\{(1, 3), (3, 1), (4, 6)\}} \][/tex]
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.